Translation Evaluation of Socio-Cultural Expression In Folklores Translated By Second Grade Students of SMA Nasrani 1 Medan - Sirumapea, Winarni; Sipayung, Kammer Tuahman; Pakpahan, Carolina (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Translation Quality Assessment (TQA) is a fast-growing sub-field of Translation Studies. The method use in this study was descriptive qualitative research with focuses in translation of socio-cultural expression in Folklores translated by second grade students of SMA Nasrani 1 Medan. The aims of this study is to describe covert and overt errors in folklores. There are five folklores selected in this study, namely Sangkuriang, Simungil Bermata Besar, Seruling Ajaib, Beruang dan Lebah, and Si Tikus. The analysis shows that in folklores translated by second grade students of SMA Nasrani 1 Medan, socio-cultural expression can be classified based on the cultural categories by Newmark (1988). There are 40 cultural words as a data in this study. The errors were identified, classified and the frequency of their occurrences was computed. For the covert errors, the Author's provenance and stance of the Source Text are Anonymous meanwhile the Translator’s provenance and stance of the target text is students. The medium category under mode ST has been written to be read and to be heard by the listeners but on the target text just to be read. Meanwhile for the overt errors, there are 60 total frequency of overt errors that consisting of not translated (32 errors), Slight change in meaning (14 errors), Significant change in meaning (9 errors), and creative translation (5errors). The result of this study can be used by translators in order to revise their translation especially in the field of literary text. The findings of this study are hoped to be of help to trainers of translating and those who interested in the field of Translation Studies.